Analisis Kandungan Gizi Beras dari Beberapa Galur Padi Transgenik Pac Nagdong/Ir36 - Dina Fitriyah; Mohammad Ubaidillah; Fariza Oktaviani (Puslitbang Sinergis Asa Professional, 2020)
Rice that is generally consumed by Indonesian people is that does not have important nutrient such as β-carotene. Therefore, the way to supply β-carotene requirement in staple foods can be done through β-carotene biofortification by genetic engineering of the rice plant. PAC Nagdong/ IR36 is transgenic Golden Rice which can produce β-carotene. The research aimed to determine some nutritional content of PAC Nagdong/ IR36 rice lines that include carbohydrate, amylose, amylopectin, protein, lipid, and β-carotene content. Amylose was measured using the iodine colorimetric method, whereas the contents of amylopectin and carbohydrates were measured using the by difference method. Protein was measured using the Bradford method, lipid was measured using Proctor and Bowen method, while β-carotene content was measured using the colorimetric method. PAC Nagdong/ IR36 rice lines had carbohydrate content between 85,06-90,16%, amylose 12,94%- 20,81%, amylopectin 69,35- 76,17%, protein 7,76-8,52 µg/µl, lipid 0,65-0,90%, and β-carotene 231,61-920,52 µg/g. Carbohydrate, protein, and β-carotene in PAC Nagdong/ IR36 were higher than TN1 rice variety (control). This indicated that PAC Nagdong/ IR36 provided better nutrition. Amylose content of Nagdong/ IR36 PAC rice was low, which donated its potential to produce fluffier rice whereas high β-carotene content could be used as a source of β-carotene that is useful in overcoming vitamin A deficiency and beneficial for health including in preventing degenerative diseases.